DAMPAK SOSIAL PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. RIAU BARAHARUM DI DESA KELESA KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Yuni Sri Astuti; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the Village District of Seberida indolent Indragiri Hulu aimed to find out how to form the Social impact of the CSR program PT. Riau Baraharum against villagers indolent. This study entitled "Social Impact of Corporate Social Responsibility (CSR) PT. Riau Baraharum in the Village District of Seberida indolent Indragiri Hulu ". The main problem in this research is Any CSR program PT. Riau Baraharum against villagers indolent and How Social Impacts resulting from CSR program PT. Riau Baraharum indolent Village District of Seberida Indragiri Hulu. The population in this study were all heads of household (husband) who make a living in the village of indolent. sampling in research is purposive sampling technique. Total population in this study in 2013 amounted to 900 heads of household, the sample taken 45 heads of household who has represented from the specified population. The method used is quantitative method Deskriptif with Quantitative and Qualitative data analysis. Data screening instruments used were observation, questionnaire, Key-informants, and systematic interviews and tabulation of data contained in a single data tabulation and diagrams. The results of the conducted research in general, the researcher can say the average respondents aged over 30 years, the majority of primary school education level, income levels Rp. 1000000-2000000, mayorits work of farmers, number of dependents on average 1-2 people. CSR program PT. Riau Baraharum good, the public relations firm RBH against indolent village well be one to keep the existence of the company RBH. In this study, the factor is the impact of demographic, socio-economic and socio-cultural.Keywords: Prgoram CSR, Social Impact,